Identification, cloning, sequencing, expression and protective capacity of the gene encoding a fimbrial protien of pasteurella multocida B:2 - Ina Salwany, Md Yasin (Fakulti Sains dan Teknologi, 2011)
Haemorrhagic septicaemia (HS), an economically important disease of cattle and buffaloes, is caused by Pasteurella multocida B:2. Vaccination against this disease is widely practiced but the protection was unclear. In order to improve the protection effectiveness of the vaccines, the causative organism has been fractionated and the various cell surface components were studied. The fimbrial proteins are particularly attractive candidate for development of recombinant vaccine because they are strong immunogens. This study was conducted to characterize and determine the antigenicity of the fimbrial protein of Pasteurella multocida B:2, followed by development of recombinant cell vaccine expressing the fimbrial protein. The study also was carried out on the potential and efficacy of Pasteurella multocida B:2 recombinant fimbrial proteins in the production of vaccine against haemorrhagic septicaemia.